ILUSTRASI DAN CERPEN - Drs. Effendi (Ars: Jurnal Seni Rupa dan Desain, 2007)
Currently, illustrative art has increased its degree: from an applied art to a fine or pure art; from arepresentative art which tends to be realistic even as realistic as photography to a non-figurativepresentation or abstract. However, in the present world o f art, it is still an applied art. So, how is its degreeincreased? Furthermore, the illustrations ncrwadays are often related to a short story or prose, one o f thegenres of literature. How does it relute to a short story?Keywords: Illustration, Kompas Newspaper